Borrelia spp. and Anaplasma phagocytophilum in ruminant ticks – Borrelia prevalence declines only in female, but not nymphal ticks feeding on cervids - Andrea Springer; Gökben Özbakış-Beceriklisoy; Anna-Katharina Topp; Julia Probst; Volker Fingerle; Christina Strube (Ticks and Tick-Borne Diseases)
Tick-borne pathogen epidemiology involves vectors, in Europe mainly Ixodes ricinus, and vertebrate hosts. Ruminants are reservoirs for Anaplasma phagocytophilum, but not for Borrelia burgdorferi sensu lato (s.l.), possibly clearing the infection from ticks. However, such clearance is epidemiologically relevant mainly in nymphal ticks. Of 1874 ticks collected from wildlife in the present study, 1535 Ixodes spp. (796 nymphs, 739 females) were tested by qPCR, with a proportion of 26.3% (nymphs: 24.5%, females: 28.3%) positive for Borrelia spp. and 87.4% for A. phagocytophilum (nymphs: 62.8%, females: 92.4%). In female Ixodes spp. from deer (N = 720), but not nymphs (N = 785), the Borrelia frequency declined significantly with increasing engorgement duration as inferred by the coxal index. Borrelia spp. differentiation revealed B. burgdorferi s.l. in nine and B. miyamotoi in one of ten successfully analysed ticks having engorged for <48 hours, but only three B. burgdorferi s.l.- vs. six B. miyamotoi-positive and one coinfected tick among ten ticks with a longer engorgement. Borrelia copy numbers showed a U-shaped relationship with engorgement duration. Increasing A. phagocytophilum frequency during the rapid feeding phase in nymphs, and increasing copy numbers in females from deer confirmed their reservoir function. Of 101 I. ricinus from cattle, 4.0% were positive for Borrelia, whereby the species could not be determined, and 42.6% for A. phagocytophilum. In comparison, 13.8% and 11.9% of 428 questing ticks from the pastures were Borrelia- and A. phagocytophilum-positive, respectively. The results imply that feeding on cervids may not reduce Borrelia prevalence in nymphs, presumably due to the low overall blood volume ingested, insufficient for Borrelia clearance in this epidemiologically relevant stage. Further studies need to confirm that deer-fed nymphs contain infectious Borrelia and maintain the infection transstadially.